Outbreaks and Epidemics of Superficial Dermatophytosis due to Trichophyton mentagrophytes Complex and Microsporum canis: An Approach to Global and Indian Scenario - Rameshwari Thakur; Avneet Singh Kalsi (New Horizons in Medicine and Medical Research Vol. 2, 2022)
Until recently, superficial dermatophytosis, also known as tinea, was considered as a minor skin infection, which was easy to treat. There used to be rare outbreaks and epidemics of superficial dermatophytosis. Lately, there is a sweeping change in the clinical presentation due to extensive, atypical and recalcitrant dermatophytosis. Treating such infections poses a great challenge to the clinicians. Dermatophytosis is a dermatophyte-caused superficial fungal infection of keratinized tissue (skin, hair, and nails) (fungus). Trichophyton, Epidermophyton, and Microsporum are three dermatophyte genera that cause it. The conventional methods of laboratory diagnosis have now been substantiated by molecular characterization. Earlier epidemics were usually due to anthropophilic dermatophytes. Now, zoophilic dermatophytes are also responsible for many outbreaks and epidemics. We need to be equipped with the tools to face the current scenario, because this depends upon the competence of the staff working in the state-of-the-art laboratories which is needed for the appropriate treatment and to study the epidemiology. Since dermatophytosis has public health importance, an appropriate diagnosis, source of infection and treatment is very crucial.